Sc1−xErxAlO3 perovskites: high-pressure synthesis, photoluminescence properties, and in vitro bioimaging. Issue 44 (8th November 2022) - Panda, Debendra Prasad; Singh, Akash Kumar; Kundu, Tapas K.; Sundaresan, A.
Abstract : In vitro bioimaging of HEK293 cells using the green luminescent Sc0.98 Er0.02 AlO3 compound. Abstract : Optical imaging carries cellular-level information and is a new paradigm as an imaging modality. Importantly, rare-earth ion-doped metal oxide imaging agents have certain advantages like sharp emission lines, long luminescence lifetimes, low cytotoxicity, and enhanced photostability over organic dyes and quantum dots and are highly desirable. In this context, we have prepared Sc1− x Er x AlO3 perovskite phosphors using the high-pressure synthetic method, which crystallize in an orthorhombic structure ( Pbnm space group). Under UV light excitation, they exhibit green luminescence with sharp emission lines and PL lifetimes in the order of microseconds. The temperature-dependent measurement suggests the high thermal photostability of the perovskite compound, which altogether indicates its potential for optical imaging. The 2% Er 3+ substituted compound incubated in HEK293 and SH-SY5Y cells exhibits very low cytotoxicity. Using a two-photon microscope, the biocompatibility of this compound in HEK293 cells was imaged, stipulating its potential biomedical application.